Problems of stability inulin and olihofructose in food storage - Lugovska, Oksana (My University, 2013)
Inulin and olihofructose can be used as purely dietary components for creation of functional food stuff with the different declared properties. Інулін і олігофруктозу можна використовувати в якості харчових компонентів для створення функціональних продуктів харчування з різними властивостями.
Keywords: olihofruktoza; foods; inulin; олігофруктоза; продукти харчування; інулін